1996
DOI: 10.1002/(sici)1096-9861(19960129)365:1<141::aid-cne11>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Activity-related features of synapse morphology: A study of endbulbs of Held

Abstract: The myelinated fibers of the auditory nerve can be divided into two separate populations on the basis of sensitivity to sound, average levels of spike activity, and central branching patterns. The synaptic endings of these populations were investigated for the presence of structural specializations that might correlate with levels of neural activity. We applied intracellular recording and staining methods in cats to analyze directly the relationship between spike activity and the structure of synapses using en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 94 publications
6
74
0
Order By: Relevance
“…Due to the somatic location of synaptic contacts between the endbulb of Held and bushy cells in the cochlear nucleus (Neises et al 1982;Ryugo et al 1996), and the previous demonstration that spontaneous EPSCs arising from the endbulb are quantal events (Isaacson & Walmsley, 1995a, we have been able to investigate absolute changes in quantal conductance and time course of AMPA and NMDA receptormediated components of EPSCs during a developmental period that covers maturation of endbulb morphology (Neises et al 1982) and spans the opening of the external ear canal and the onset of sensory input to bushy cells. Over this period of development, we have demonstrated that quantal AMPA EPSCs show an increase in conductance without major changes in their time course, while quantal NMDA EPSCs show a decrease in conductance with a major change in decay time course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the somatic location of synaptic contacts between the endbulb of Held and bushy cells in the cochlear nucleus (Neises et al 1982;Ryugo et al 1996), and the previous demonstration that spontaneous EPSCs arising from the endbulb are quantal events (Isaacson & Walmsley, 1995a, we have been able to investigate absolute changes in quantal conductance and time course of AMPA and NMDA receptormediated components of EPSCs during a developmental period that covers maturation of endbulb morphology (Neises et al 1982) and spans the opening of the external ear canal and the onset of sensory input to bushy cells. Over this period of development, we have demonstrated that quantal AMPA EPSCs show an increase in conductance without major changes in their time course, while quantal NMDA EPSCs show a decrease in conductance with a major change in decay time course.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that acoustic inputs are the primary determinants of developmental changes in synaptic transmission, since basic tonotopic map formation can form in the brainstem auditory pathways by postnatal day 5 (Kandler & Friauf, 1993) and auditory nerve fibres are spontaneously active in the absence of acoustic stimulation, even before ear canal opening (Liberman, 1991). It is possible that this spontaneous activity is important in developmental changes in synaptic transmission, as endbulbs of high spontaneous activity fibres are larger and contain more synaptic specializations than endbulbs of low spontaneous activity fibres (Ryugo et al 1996). Such an increase in the number of specializations may be due to NMDA receptor activation and the splitting of existing synapses (Dyson & Jones, 1984;Edwards, 1995), and may underlie the increased AMPA quantal content seen in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this work has focused on the abnormal ultrastructural features of endbulbs in congenitally deaf animals (Ryugo et al 1996;Ryugo et al 1997;FIG. 9.…”
Section: Alterations Of Synaptic Transmission In the Auditory Nerve Amentioning
confidence: 99%
“…They ramify within the small cell cap, a region of small cells that lie beneath the granule cell domain. Light microscopic, drawing tube reconstruction exhibit different innervation characteristics with the IHCs [99,111], give rise to greater collateral branching in the AVCN [51], emit collaterals that preferentially innervate the small cell cap [100,177], and manifest striking specializations in the large axosomatic endings, the endbulbs of Held [185] and their synapses [178].…”
Section: Sr and Central Correlatesmentioning
confidence: 99%